Validation of a GEANT4 based Monte Carlo code for voxelized geometries for patient-oriented mammography dosimetry - Werner, Rahel-Debora (2023)
This work presents a preliminary validation of a Monte Carlo radiation transport code capable of simulating radiation transport on voxelized structures. Field size and depth dose were measured at Physikalisch-Technische Bundesanstalt (PTB) Braunschweig for mammography tungsten spectra of 30 kVp and 50kVp. Four different collimators were used to vary the field size between 0.94 cm and 4.74 cm of aperture radius. Depth dose was measured between 0 cm and 2 cm depth using a PTW PMMA phantom and two PTW ion chambers. Monte Carlo simulations were performed using the Geant4 toolkit (EM standard physics). Maximum relative difference in field size effect between experiment and simulation was 2.1%. In the case of the depth-dose study, it was 5.6%. The simulations used in this study have been shown to provide accurate estimations of quantities relevant to the calculation of dosimetric quantities.